Nicotinamide Adenine Dinucleotide Phosphate Oxidases and Metabolic Dysfunction-Associated Steatotic Liver Disease - Vittoria Cammisotto; Emanuele Valeriani; Pasquale Pignatelli; Francesco Violi (Antioxidants)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is characterized by lipid accumulation in the liver due to an excess in their supplies or an impairment in their management. While some patients remain stable for years, a proportion of them progress up to steatohepatitis (MASH). MASLD links with systemic pathways being associated with metabolic and non-metabolic diseases. Although liver lipid accumulation represents the first hit for MASLD, the pathophysiology of its development and progression to MASH remains not completely understood. Oxidative stress has received particular attention in recent years, as most of the oxidative process occurs in the liver, which is also the target of oxidative stress-induced damage. Growing evidence linked the activity of nicotinamide adenine dinucleotide phosphate (NADPH) oxidases (NOX) to the increased liver production of reactive oxygen species up to liver damage and fibrosis. NOX acts both in hepatocytes and in non-parenchymal hepatic cells, contributing to hepatocyte lipotoxicity, impaired hepatic microcirculation, hepatic stellate, and mesenchymal stem cells activation and proliferation. This review aims to summarize the current knowledge on the involvement of oxidative stress in the MASLD–MASH transition, focusing on the role of NOX isoforms, and to suggest targeting NOX as a therapeutic approach in MASLD.